Miyakella nom. nov., a replacement name for Miyakea Manning, 1995, (Crustacea: Stomatopoda: Squillidae), preoccupied by Miyakea Marumo, 1933 (Insecta: Lepidoptera: Crambidae) - Ahyong, Shane T.; Low, Martyn E. Y. (Zootaxa, 2013)
Manning (1995: 213), in a monograph of the stomatopod crustaceans of Vietnam, proposed the name Miyakea for a genus of Indo-West Pacific stomatopods corresponding to the nepa group of species in Oratosquilla Manning, 1968: Squilla nepa “Latreille, 1828” (type species), and Squilla holoschista Kemp, 1911 (Manning 1971: 2–4, 7, 8; Ahyong 2001: 278; Ahyong et al. 2008: 137). Squilla nepa has long been attributed to “Latreille, 1828” but should be correctly attributed to “Latreille, in Latreille, Le Peletier, Serville & Guérin, 1828”, as Low & Ng (2012: 49) argued for the identical case of the name Cardiosoma in the same publication of Latreille (in Latreille et al. 1828).